High-Grade Serous Carcinoma Resulting From Rectal Endometriosis and Complicated With Ovarian Cancer - Song, Li; Xing, Aiyan; Li, Qiuju; Wang, Guoyun (Frontiers in Oncology, 2019)
Endometriosis is one of the most common benign gynecological diseases. it has malignant behaviors such as invasion, implantation and recurrence, and has the characteristics similar to malignant tumors. Epidemiological, clinicopathological, molecular biological and genetic evidence suggests that endometriosis can be malignant. Endometriosis-associated malignancy (EAM) was closely correlated with endometriosis in histology. EAM arise from atypical endometriosis as an intermediate lesion between endometriosis and cancer. About 80 per cent of EAM is located in the ovary, also known as endometriosis-associated ovarian cancer (EAOC). EAOC with clear cell adenocarcinoma and endometrioid carcinoma as the main pathological types of a special group of ovarian epithelial carcinoma. Extragonadal endometriosis is rare. No association between endometriosis and high-grade serous ovarian cancer or mucinous ovarian cancer has been reported to date. We first report a very rare case of high-grade serous carcinoma arising from endometriosis of the rectum complicated with ovarian cancer. A 63-year-old Chinese woman was admitted with the complaint of abdominal distention. We diagnosed the patient as having ovary carcinoma, and planned to perform cytoreductive surgery. During the operation, we found a solid mass of 12cm in the anterior wall of the rectum containing chocolate-like fluid. Histopathological examination after surgery revealed high-grade serous carcinoma arising from endometriosis of the rectum complicated with ovarian cancer. The patient received 6 cycles of chemotherapy postoperatively, consisting of carboplatin and paclitaxel, and showed no recurrence.